2014
DOI: 10.30782/uluvfd.163480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Culture on Growth Performance, Haematological and Biochemical Indices of New Zealand White Rabbits

Abstract: Effect of Sacchoromyces cerevisiae live yeast culture on growth performance, haematological and biochemical indices of rabbits was studied with 6-7 weeks old New Zealand white rabbits. Thirty male rabbits were divided equally into 3 groups; I.control group (basal diet), II.group (added S. cerevisiae, 2 g/kg diet) and III.group (added S. cerevisiae, 4 g/kg diet). Blood samples were obtained via ear venipuncture on the 85th day of feeding yeast of rabbits. No significant difference was observed in blood composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
3
5
1
Order By: Relevance
“…Total protein level results were similar to our results (11,15,16), and higher than another study (14), while the parameters were reported parallel with our results.…”
Section: Serum Biochemical Analysis Can Play An Importantsupporting
confidence: 92%
See 2 more Smart Citations
“…Total protein level results were similar to our results (11,15,16), and higher than another study (14), while the parameters were reported parallel with our results.…”
Section: Serum Biochemical Analysis Can Play An Importantsupporting
confidence: 92%
“…The previous studies were reported differences in glucose levels that serum glucose levels in live animals can be affected because of different factors such as blood collection procedure environmental conditions and stress. In this parallel, the glucose level results of our study were similar to those of the previous studies (11,15,16), while the glucose result was lower than another study (17).…”
Section: Serum Biochemical Analysis Can Play An Importantsupporting
confidence: 91%
See 1 more Smart Citation
“…An increase in the concentrations of haematocrit and haemoglobin, whereas a reduction in cholesterol was observed in rabbits fed S. cerevisiae supplemented diet with 2 g kg −1 feed (Seyidoglu et al ) (Fig. ).…”
Section: Probiotic Yeast For Rabbitsmentioning
confidence: 94%
“…Further, decrease in cholesterol content of eggs of laying hens and broilers diets containing yeasts was reported by Yalçın et al [20] and Yıldız et al [21] . Seyidoğlu and Galip [22] and Seyidoğlu et al [23] were conducted to evaluate the effect of Saccharomyces cerevisiae on the serum biochemical parameters in rabbits. The diets with the yeast reduced serum HDL cholesterol and triglycerides on the 90 th feeding day.…”
Section: Discussionmentioning
confidence: 99%